Pengaruh Alat Peraga Tiga Dimensi Sistem Peredaran Darah Manusia terhadap Hasil Belajar Siswa SMA - Fahruddin Arfianto (Anterior Jurnal, 2015)
Learning by using aids will greatly help students understand the concepts contained in learning materials. The aid in learning circulation of blood is very needed by students to understand directly the blood circulatory system in humans. The purpose of this study was to determine the effects of the three-dimensional visual aids in learning outcomes of material human blood circulatory system on high school students. The method used in this study was pretest-posttest control group design, in this design, there were two groups of randomly selected, and then the groups given a pretest to determine the initial condition is the difference between the experimental group and the control group. This study was conducted in period from April to May 2015. The sample of this study was the students of class XI in SMA Muhammadiyah 1 Palangka Raya in odd semestre. The study was taken two classes, namely as an experimental class and control class. The number of the students of control class was 29 students, and for experiments class was 21 students. The data collected by a test with the form of multiple choice questions to measure student learning outcomes. The result of this study showed that the three-dimensional aids in learning human blood circulatory system had significant effect on improving students’ learning outcomes, based on t-test using SPSS software version 16.0. So, it can be concluded that the use of the three-dimensional aids in learning human circulatory system will improve the students’ learning outcomes.